Potencial fotoprotetor e genoprotetor da própolis vermelha produzida por apis mellifera no semiárido do rio grande do norte, brasil - Menezes, Manuela Costa de (2019)
The objective of this study was to evaluate the levels of phenols, total flavonoids, as well as the antioxidant, genoprotective and photoprotective activities of the red propolis ethanolic extract produced by Apis mellifera. Different concentrations of the extract were evaluated in vitro by spectrophotometry. The photoprotective effect of the extract was evaluated in vivo in 30 Wistar rats divided into three groups: Group I - the skin received no topical application of the extract and was not submitted to ultraviolet irradiation; Group II - the skin was not subjected to topical application of extract and were irradiated; Group III - skin underwent topical application of extract and were irradiated. The skin was evaluated macroscopically and the density of inflammatory cells, mast cells, necrotic cells and collagen fibers was quantified. The extract presented high levels of phenols and flavonoids with antioxidant and genoprotective capacity, protecting the skin from irradiation. In group II, erythemas, blisters and superficial crust were observed. No significant differences in mean values of mast cell density and collagen fibers did not differ between groups I and III. It was concluded that the ethanolic extract of red propolis exerted genoprotective and photoprotective effects by promoting satisfactory absorbances of ultraviolet radiation and was able to protect the skin from lesions induced by UVB irradiation.